Exploring crop genomics: role of molecular markers in identifying genetic diversity and characterization - G, Renuk; T, Shankar; M, Venkateshwarlu.; T Salve , Jayesh; D . A, Dhale; T, Ugandhar (International Journal of Biological Research, 2024)
and facilitating germplasm characterization for crop improvement. Understanding and harnessing crop genetic diversity are paramount with the escalating demand for sustainable agricultural practices and the need to address global food security challenges. Molecular markers have emerged as powerful tools enabling precise identification, characterization, and utilization of genetic resources for crop enhancement.The paper provides an in-depth analysis of various molecular marker techniques, encompassing DNA-based markers such as single nucleotide polymorphisms (SNPs), simple sequence repeats (SSRs), and amplified fragment length polymorphisms (AFLPs), as well as RNA-based markers like expression sequence tags (ESTs) and microRNAs. By elucidating genetic relationships, population structure, and phylogenetic analysis, these markers facilitate the conservation and utilization of crop germplasm. Moreover, the review highlights recent advancements in high-throughput genotyping technologies and bioinformatics tools, which have revolutionized crop genomic research. These advancements enable comprehensive genome-wide analyses, accelerating breeding efforts for the development of improved crop varieties with enhanced traits such as yield, quality, and stress tolerance. Integration of molecular marker-assisted selection (MAS) into breeding programs further enhances the efficiency and precision of crop improvement strategies.Despite the significant contributions of molecular markers to crop genomics, challenges persist. The review addresses these challenges and discusses potential solutions, emphasizing the importance of collaborative efforts, data sharing, and interdisciplinary research endeavors. By overcoming these hurdles, the agricultural community can fully harness the potential of genomics for sustainable crop improvement, thus addressing global food security challenges in the face of changing environmental conditions and population growth.In conclusion, understanding the role of molecular markers in crop genomics is crucial for optimizing breeding strategies, conserving genetic resources, and developing resilient crop varieties to meet the demands of a growing population and ensure food security in a changing world.